2022
DOI: 10.2460/ajvr.22.01.0014
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting injectable methadone (methadone-fluconazole) provides safe and effective postoperative analgesia in a randomized clinical trial for dogs undergoing soft tissue surgery

Abstract: OBJECTIVE To assess the pharmacokinetics, clinical efficacy, and adverse effects of injectable methadone with the pharmacokinetic enhancer fluconazole (methadone-fluconazole), compared with the standard formulation of injectable methadone, in dogs after ovariohysterectomy. We hypothesized that 2 doses of methadone-fluconazole would provide 24 hours of postoperative analgesia. ANIMALS 3 purpose-bred dogs (pharmacokinetic preliminary study) and 42 female dogs from local shelters (clinical trial) were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…But it is still important to note the elevated MIC values and evidence for multi-drug resistance in these commensals (Figure 4A). These data can also help assess the risk and predicted efficacy of using antifungal drugs in dogs for effective treatment, including prophylaxis and longterm treatments (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…But it is still important to note the elevated MIC values and evidence for multi-drug resistance in these commensals (Figure 4A). These data can also help assess the risk and predicted efficacy of using antifungal drugs in dogs for effective treatment, including prophylaxis and longterm treatments (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The half‐life of methadone after intravenous injection has been shown to be relatively short in dogs suggesting a dosing interval of 4 hours (Kukanich et al., 2005; KuKanich & Borum, 2008; Schmidt et al., 1994). The pharmacokinetics of sc methadone suggest a dosing interval of 4 to 6 hours to maintain methadone concentrations above the range associated with anti‐nociception and central opioid effects (17 to 21 ng/mL) which will also be dependent on the dose administered (Bieberly et al., 2022; KuKanich et al., 2021). Although some studies have demonstrated a longer terminal half‐life after subcutaneous administration, this occurred at low concentrations below those expected to be effective (Ingvast‐Larsson et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, methadone is approved for canine use in some countries at a dosage of 0.5–1 mg/kg IV, IM, SC, but some veterinarians suggest that this dose is too high in dogs. Clinical trials conducted by our research team demonstrated methadone 0.5 mg/kg SC q4 h provided effective and well‐tolerated analgesia in dogs undergoing soft tissue surgery, n = 33 total dogs (Bieberly et al., 2022; KuKanich et al., 2020).…”
Section: Introductionmentioning
confidence: 99%